Answer
y = 2x
Explanation
The first thing is to find the gradient of the line.
Gradient = Δy/Δx
= (4--2)/(2--1)
= 6/3
= 2
Now a general point (x, y) and one of thegiven points.
(y - 4)/(x - 2) = 2
y - 4 = 2(x - 2)
y = 2x - 4 + 4
y = 2x + 0
y = 2x
Answer:
Divide both sides by 3.
(x+2)^2=16
Square root both sides.
x+2= ± 4 (plus OR minus, can be either so we have to include both)
Minus 2 from both sides.
x=-2 ± 4
Add and minus the 4 to -2.
x = -2-4 = -6 and x=-2+4 = 2
Answer:
-12
Step-by-step explanation:
Answer:
Step-by-step explanation:
8 because 2 and 2/3 times 3 equals 8/3 times 3 and the threes cancel out and there is a 8 left.
Well, if we divide 3.22 by 14 we get 0.23
0.23 +0.15 is 0.38
the answer would be $0.38